2009
DOI: 10.1002/dneu.20720
|View full text |Cite
|
Sign up to set email alerts
|

Timing and duration of developmental nicotine exposure contribute to attenuation of the tadpole hypercapnic neuroventilatory response

Abstract: The ability for air-breathing vertebrates to adjust ventilation in response to increased CO2 (hypercapnia) is fundamental to maintaining pH homeostasis. Developmental nicotine exposure has been shown to impair tadpole neuroventilatory responses to hypercapnia following 8-12 wk of exposure. It is not clear, however, to what extent the timing of exposure during development and/or the duration over which the exposure takes place contribute to this impairment. Here tadpoles were exposed to 30 μg/L of nicotine for … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
13
0

Year Published

2009
2009
2015
2015

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(14 citation statements)
references
References 37 publications
1
13
0
Order By: Relevance
“…This was similar to studies looking at the effect of chronic nicotine exposure on hypercapnic ventilation, where early metamorphic tadpoles exhibited an impaired hypercapnic response after 3-wk nicotine exposure, whereas late metamorphic tadpoles required 10-wk exposure to exhibit the same impairment (Brundage and Taylor, 2009). The effects of acute nicotine exposure, however, are opposite in that they increase with bullfrog development (Brundage et al, 2010).…”
Section: Discussionsupporting
confidence: 82%
See 4 more Smart Citations
“…This was similar to studies looking at the effect of chronic nicotine exposure on hypercapnic ventilation, where early metamorphic tadpoles exhibited an impaired hypercapnic response after 3-wk nicotine exposure, whereas late metamorphic tadpoles required 10-wk exposure to exhibit the same impairment (Brundage and Taylor, 2009). The effects of acute nicotine exposure, however, are opposite in that they increase with bullfrog development (Brundage et al, 2010).…”
Section: Discussionsupporting
confidence: 82%
“…We have previously shown that 10 wk of nicotine exposure has no effect on normoxic/normocapnic gill neuroventilation nor does it affect the integrity of the isolated bullfrog brainstem lung activity over the duration of the experiment (Taylor et al, 2008; Brundage and Taylor, 2009). Here we see that 10-wk nicotine exposure did have a significant effect on gill burst activity.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations